Gypsies in 19th-Century French Literature: The Paradox in Centering the Periphery - Udasmoro W. (K@ta: A Biannual Publication on the Study of Language and Literature, 2015)
The issues of liberty and views of the “Other” were common in 19th-century French literary discourse. In many aspects, the “Other” appeared to hold a position of strength. In literature, Prosper Mérimée and Victor Hugo attempted to centralize gypsy women through their narratives, even though gypsies (as with Jews) had been marginalized (though present) throughout French history. Mérimée’s Carmen and Hugo’s Notre Dame de Paris presented new central perspectives on the peripheral, which in this context should be understood to mean gypsies. This research paper attempts to answer the following questions: What ideology lies behind both stories’ centralization of the peripheral gypsy women? How do the authors portray gypsy women? The goal of this article is to explore the operations of power in a gender-relations context, focusing on the construction of gypsy women in two 19th-century French novels.